PENGARUH PROFITABILITAS TERHADAP PENGHINDARAN PAJAK DENGAN VARIABEL MEDIASI LEVERAGE PADA PERUSAHAAN MIGAS TERDAFTAR DI BEI PADA TAHUN 2017-2019 - Meysi BR Napitupulu; Francis M. Hutabarat (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
Abstract, The purpose of this study is to discuss how the influence of profitability on tax avoidance by using leverage as a mediating variable in oil and gas companies listed on the Indonesia Stock Exchange from 2017-2019 is an important target to be clear and precise. The population of this research is 7 oil and gas companies that have been listed on the IDX since the 2017-2019 period as the main focus in conducting research. Researchers conducted research through descriptive analysis and then processed it with software SPSS. Tax avoidance as the dependent variable (Y) and profitability as the independent variable with leverage as the mediating variable. This research was conducted using the F test, T test, and Determination Test (R2). The results of this study find that profitability has no effect which shows significant results on tax avoidance, while leverage is inversely related to profitability, leverage has a significant effect on tax avoidance, also profitability itself proves that there is an effect that shows significant results on tax avoidance with using leverage as a mediating variable.